2016
DOI: 10.1111/1758-2229.12372
|View full text |Cite
|
Sign up to set email alerts
|

Intraclonal genome diversity of the major Pseudomonas aeruginosa clones C and PA14

Abstract: SummaryBacterial populations differentiate at the subspecies level into clonal complexes. Intraclonal genome diversity was studied in 100 isolates of the two dominant P seudomonas aeruginosa clones C and PA14 collected from the inanimate environment, acute and chronic infections. The core genome was highly conserved among clone members with a median pairwise within‐clone single nucleotide sequence diversity of 8 × 10−6 for clone C and 2 × 10−5 for clone PA14. The composition of the accessory genome was, on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
55
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(58 citation statements)
references
References 31 publications
(42 reference statements)
3
55
0
Order By: Relevance
“…Nonsynonymous SNPs present in the pangenome were less frequent among SNPs (N/S ϭ 0.13; P ϭ 2.5 ϫ 10 Ϫ5 by Fisher's exact test) than expected from the N/S ratio of 0.23 derived from whole-genome sequence comparisons (27), whereas nonsynonymous SNPs were overrepresented among the SNPs not known from the pangenome analysis (N/S ϭ 0.58; P ϭ 2.1 ϫ 10 Ϫ21 ). These data indicate that changes in the coding sequences of targets of antimicrobials are normally counterselected because these genes are probably essential for P. aeruginosa.…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Nonsynonymous SNPs present in the pangenome were less frequent among SNPs (N/S ϭ 0.13; P ϭ 2.5 ϫ 10 Ϫ5 by Fisher's exact test) than expected from the N/S ratio of 0.23 derived from whole-genome sequence comparisons (27), whereas nonsynonymous SNPs were overrepresented among the SNPs not known from the pangenome analysis (N/S ϭ 0.58; P ϭ 2.1 ϫ 10 Ϫ21 ). These data indicate that changes in the coding sequences of targets of antimicrobials are normally counterselected because these genes are probably essential for P. aeruginosa.…”
Section: Resultsmentioning
confidence: 84%
“…The emergence of a premature termination codon will result in most cases in the loss of protein function, unless some translational read-through is promoted. The sequencing of an individual 6-to 7-Mbp large P. aeruginosa genome will typically identify one or two stop mutations (24,27). Amplicon sequencing of the 361 CF isolates in the 17 loci uncovered a significantly higher rate of stop mutations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, 100 genome sequences of P. aeruginosa clone C and clone PA14 isolates were sequenced on a SOLiD 5500XL system with a 75‐bp read length. Reads were aligned to PAO1 reference genome using the program novoaligncs (http://www.novocraft.com).…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, recent studies have suggested that there must be some mechanism for gene loss to counterbalance these gene acquisitions [2,3]. Furthermore, several studies have shown that most of these imported genomic regions usually come from closely-related genomes but the precise origin cannot be identified [1,[4][5][6]. Therefore, it has been difficult to perform detailed analyses of the recombination processes that result in the acquisition of new genes via naturally occurring horizontal gene transfer (HGT).…”
Section: Introductionmentioning
confidence: 99%